2013
DOI: 10.1186/1475-9276-12-6
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of the effects of living in extremely poor neighborhoods by health insurance: breast cancer care and survival in California, 1996 to 2011

Abstract: BackgroundWe examined the mediating effect of health insurance on poverty-breast cancer care and survival relationships and the moderating effect of poverty on health insurance-breast cancer care and survival relationships in California.MethodsRegistry data for 6,300 women with breast cancer diagnosed between 1996 and 2000 and followed until 2011 on stage at diagnosis, surgeries, adjuvant treatments and survival were analyzed. Socioeconomic data were obtained for residences from the 2000 census to categorize n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 68 publications
4
23
2
Order By: Relevance
“…This finding is concordant with earlier reports showing longer waiting times for patients with a lower SES, e.g. in breast cancer [28]. However, low SES was also associated with a higher stage (35% stage IV in low SES versus 32% stage IV in high SES) and were therefore treated with chemoradiation more frequently.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is concordant with earlier reports showing longer waiting times for patients with a lower SES, e.g. in breast cancer [28]. However, low SES was also associated with a higher stage (35% stage IV in low SES versus 32% stage IV in high SES) and were therefore treated with chemoradiation more frequently.…”
Section: Discussionsupporting
confidence: 91%
“…Studies in the United States have shown shorter survival time of women who use Medicaid (public health system for people under the poverty line), compared to those who have private health insurance 15,22 . Studies conducted in Brazil and other Latin American countries found a positive association between socioeconomic status of the patient and breast cancer survival 6,23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to staging, a number of studies identified, as influencing factors of the relation between socioeconomic status and survival, the access to health services for screening, diagnosis and treatment, and, in a smaller proportion, the histologic type and grade, biomarkers such as hormone receptors, and the overall health status of the patient in relation to the presence of morbid conditions 16 . The social status of the area of residence is also identified, with its effect mediated mainly by the patient having or not having private health insurance 22 . In most studies carried out in the United States, socioeconomic status and race/skin color had independent effects in breast cancer survival 34 .…”
Section: Discussionmentioning
confidence: 99%
“…First, income has been observed to be strongly associated with breast cancer care and survival in the US, but not in Canada (Gillan et al, 2012;Gorey, 2009;McKenzie & Jeffreys, 2009). Second, in the US women with private HI or Medicare coverage are more likely to receive better care than are women with arguably less adequate coverage such as that provided through the Medicaid programs of many states or none (Coburn et al, 2008;Gorey et al, 2013;Schueler, Chu, & Smith-Bindman, 2008;Subramanian et al, 2011). And third, studies of breast cancer survival in Canada and the US have consistently observed better survival in Canada among the poor, but no systematic differences within middle or upper socioeconomic strata (Gorey, 2009).…”
mentioning
confidence: 99%